Acetate-Inducing Metabolic States Enhance Polyhydroxyalkanoate Production in Marine Purple Non-sulfur Bacteria Under Aerobic Conditions - Higuchi-Takeuchi, Mieko; Numata, Keiji (Frontiers in Bioengineering and Biotechnology, 2019)
Polyhydroxyalkanoates (PHAs) are a family of biopolyesters that a variety of microorganisms accumulate as carbon and energy storage molecules under starvation conditions in the presence of excess carbon. Anoxygenic photosynthetic bacteria exhibit a variety of growth styles and high PHA production activity. Here, we characterized PHA production by marine purple nonsulfur bacteria under different growth conditions. Unlike the well-studied PHA-producing bacteria, nutrient limitation is not required for PHA production in marine purple nonsulfur bacteria. We found that marine purple nonsulfur bacteria did not accumulate PHA under aerobic conditions in the presence of malate and pyruvate. Interestingly, PHA accumulation was observed upon the addition of acetate under aerobic conditions but was not observed upon the addition of reductants, suggesting that an acetate-dependent pathway is involved in PHA accumulation. Gene expression analysis revealed that the expression of isocitrate dehydrogenase in the tricarboxylic acid (TCA) cycle decreased under aerobic conditions and increased with the addition of acetate, indicating that TCA cycle activity is involved in PHA production under aerobic conditions. We also found that expression of PdhRrs, which belongs to the GntR family of transcription regulators, in Rhodovulum sulfidophilum was upregulated upon the addition of acetate. Taken together, the results show that the changes in the metabolic state upon the addition of acetate, possibly regulated by PdhR, are important for PHA production under aerobic conditions in marine purple nonsulfur bacteria.